A review of the genus Phaneroserphus (Hymenoptera, Proctotrupidae) in North and Central America with the description of a new species - Kolyada, Victor A.; Chemyreva, Vasilisa G. (Zootaxa, 2023)
Phaneroserphus mesamericanus sp. n. is described from Central America. A revised diagnosis of Phaneroserphus and an illustrated identification key for New World species of the genus are provided.